2017
DOI: 10.1136/rmdopen-2016-000371
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and network meta-analysis of the efficacy and safety of tumour necrosis factor inhibitor–methotrexate combination therapy versus triple therapy in rheumatoid arthritis

Abstract: ObjectiveClinical trials have not consistently demonstrated differences between tumour necrosis factor inhibitor (TNFi) plus methotrexate and triple therapy (methotrexate plus hydroxychloroquine plus sulfasalazine) in rheumatoid arthritis (RA). The study objective was to estimate the efficacy, radiographic benefits, safety and patient-reported outcomes of TNFi–methotrexate versus triple therapy in patients with RA.MethodsA systematic review and network meta-analysis (NMA) of randomised controlled trials of TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 123 publications
1
18
0
2
Order By: Relevance
“…Based on these previous results, one could hypothesize that the risk of infection would be less with triple therapy compared to TNFi plus MTX treatment. A recent network meta‐analysis of 33 RCTs on MTX‐inadequate responders showed a strikingly low odds ratio (OR) of overall infection in the triple therapy group compared with TNFi plus MTX treatment (OR 0.08 [95% credible interval 0.00–0.57]) (7). However, this estimate may have been exaggerated due to indirect comparisons of the included RCTs and/or small sample sizes and low event numbers in trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these previous results, one could hypothesize that the risk of infection would be less with triple therapy compared to TNFi plus MTX treatment. A recent network meta‐analysis of 33 RCTs on MTX‐inadequate responders showed a strikingly low odds ratio (OR) of overall infection in the triple therapy group compared with TNFi plus MTX treatment (OR 0.08 [95% credible interval 0.00–0.57]) (7). However, this estimate may have been exaggerated due to indirect comparisons of the included RCTs and/or small sample sizes and low event numbers in trials.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review on observational studies has suggested an increased risk of serious infections associated with bDMARDs compared to cDMARDs (6). A recent network meta‐analysis of RCTs reported an exceptionally greater risk of infection in the TNFi plus MTX group compared to the triple therapy group (7), but this study is likely limited by relying mostly on indirect comparisons of the 2 groups in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…There is already plenty of evidence that addition of a bDMARD to MTX (on failure of monotherapy) is better in the short term than addition of a cs-DMARD. A network meta-analysis of 33 trials has shown the superiority of b-DMARDs at 6 months in achieving higher disease control, that is, in the American College of Rheumatology 70% response criteria (ACR70) 2. Similarly, a meta-analysis of eight such trials demonstrated similar benefits with bDMARDs at 6 months, but the differences disappeared at 24 months 3.…”
mentioning
confidence: 99%
“…As Dr Ahmed mentioned, previous research has been performed into treatment options after MTX failure, including the mentioned network meta-analysis based on clinical trials 2. These trials mostly included a selected population and reported response to one or at most two treatment options, either including a biologic disease modifying anti-rheumatic drug (bDMARD) or conventional synthetic (cs) DMARD triple therapy.…”
mentioning
confidence: 99%